Percepção de apoio familiar na adolescência e sua relação com ansiedade generalizada e depressão maior. - Lins, Jhérsyka Evelin Mendes (2019)
Anxiety and depression disorders in adolescents are becoming growing and worrying public health problems that may be influenced by established family relationships. Therefore, the aim of the present study was to investigate the relationship between the perception of family support and perceptions of generalized anxiety and major depression in adolescents. The study was divided into two articles, the first being a systematic review, gathering recent studies evaluating family relationships and the presence of anxiety and/or depression symptoms in adolescents. The second article, in turn, consists of an empirical study on the relationship between the perception of family support and the perception of generalized anxiety disorder and major depression of 250 students, from both genders, from the state school of Recife-PE. The sample was stratified from the six Political-Administrative Regions - RPA's of the Recife City Hall, being investigated the RPA's I, II, III and VI. Collectively, we used as screening tools some items from the Health Behavior in School-aged Children (HBSC) concerning family support (04 items) and the Spense Children's Anxiety Scale (SCAS) regarding generalized anxiety (06 items) and the Children's Depression Inventory (CDI - 27 items). The extraction of Cronbach's alpha from each instrument allowed identifying from satisfactory to high internal consistency indices (α = 0.86; α = 0.701 and α = 0.925, respectively). From the systematic review, it was possible to identify that factors such as: experiencing maternal overprotection, parental authoritarianism, parents with disorders, high level of conflict between parents and children, physical abuse and poor family functioning have a negative influence on adolescents' mental health. The sociodemographic profile of the adolescents participating in the empirical study revealed that most of the students were female (67.6%), low socioeconomic family level (47.2%), enrolled in the first year of high school (40%), self-declared. brown (50.4%), from RPA I (63.6%) and living with mother, father and siblings. It was possible to verify a relationship between the perception of family support and the perceptions of generalized anxiety and major depression. Correlation analysis (Pearson's r) indicated significant relationships between total generalized anxiety perception score, age (r = 0.178, p <0.01) and gender (r = 0.315, p <0, 01), which confirms what was previously observed when comparing the means in terms of greater perception of anxiety symptoms in 15-year-old and female adolescents. The total score for the perception of major depression was significantly related to gender (r = 0.201, p <0.01), with the total score for generalized anxiety perception (r = 0.542, p <0.01) and that of supportive perception. family history (r = -0,450, p <0.01). These results reinforce the evidence that the greatest perception of depressive symptoms is in females, in adolescents who are more anxious and who have less family support. It is considered important that further investigations on this subject be carried out, since although studies on depression and anxiety in adolescents have increased in recent years, the results show that they are still recent and scarce in our country.